Analysis of Volatility and Liquidity Before and After Broker ID Anonymization - Hasan Wahid; Asri Jaya; Sahabuddin Nanda (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the impact of Broker ID's anonymization policy on stock price volatility and market liquidity in LQ45 index companies on the Indonesia Stock Exchange. This study uses a comparative quantitative method with an event study approach during the three-month observation period before and after the policy (September 2021- February 2022). Based on the results of the Wilcoxon signed-rank test, significant differences were found in the two variables between the period before and after the implementation of the policy. The results show that the average volatility has decreased sharply by 171.72%, which indicates that the market has become more stable and price fluctuations are more controlled in the absence of signals from the broker's identity. In contrast, market liquidity decreased by 4.36%, reflecting reduced speculative activity and herding behavior due to the loss of information transparency. In conclusion, this policy is effective in reducing price volatility and creating stability, but it has an impact on liquidity contraction as investors become more cautious in transactions.